Aspirin for primary prevention of cardiovascular outcomes in diabetes mellitus: An updated systematic review and meta-analysis. (December 2020) - Khan, Safi U; Ul Abideen Asad, Zain; Khan, Muhammad U; Talluri, Swapna; Ali, Farman; Shahzeb Khan, Muhammad; Lone, Ahmad N; Mookadam, Farouk; Krasuski, Richard A; Kaluski, Edo
Background: The safety and efficacy of aspirin for the primary prevention of cardiovascular disease in patients with diabetes mellitus remains controversial. Design: A meta-analysis to investigate the effects of aspirin for the prevention of cardiovascular disease in diabetes mellitus. Methods: Ten randomized controlled trials were selected using MEDLINE, EMBASE and CENTRAL databases until 27 September 2018. Risk ratios (RRs) with 95% confidence intervals (CIs) and risk differences (RDs) reported as incident events per 1000 person-years were calculated. Results: In 33, 679 patients, aspirin did not significantly reduce the risk of major adverse cardiovascular outcomes (RR 0.93, 95% CI 0.87–1.00, P = 0.06; RD −0.68 incident cases per 1000 person-years (95% CI −1.54, 0.17)), cardiovascular mortality (RR 0.95, 95% CI 0.83–1.09, P = 0.49; RD 0.11 incident cases per 1000 person-years (95% CI −0.80, 1.02)), myocardial infarction (RR 0.91, 95% CI 0.75–1.11, P = 0.36; RD −0.66 incident cases per 1000 person-years (95% CI −2.07, 0.75)), or stroke (RR 0.91, 95% C, 0.76–1.10, P = 0.33; RD −0.55 incident cases per 1000 person-years (95% CI −1.57, 0.47)). There was a significantly higher risk of total bleeding associated with aspirin (RR 1.29, 95% CI 1.07–1.55, P = 0.01; RD 1.49 incident cases per 1000 person-years (95% CI 0.36, 2.61)). Conclusion: The use of aspirin for primary prevention of cardiovascular disease in patients with diabetes mellitus increases the risk of total bleeding without reducing the risk of major adverse cardiovascular outcomes.